Pelaksanaan Penilaian Pembelajaran Tematik di MIs Nurul Hidayah Rawa Cangkuk Kec. Medan Denai - Harri Gusnirwanda; Efrina Mora (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
Assessment is very important to be carried out by the teacher, because without an assessment the teacher will not be able to see the competencies of students who have developed or not at all. So assessment is very useful for teachers if done. One of the benefits is that the teacher will know that the material that has been taught during learning is carried out whether students can understand it or not. Educational Assessment Standards are criteria regarding mechanisms, procedures and instruments for assessing student learning. This study aims to describe the ability of teachers to conduct thematic learning assessments. Based on the results of the research, it shows that the implementation of the assessment based on the 2013 curriculum has not been fully implemented by MIS Nurul Hidayah Rawa Cangkuk Kec. Denai Field. The data obtained will be very useful for determining steps or policies related to assessment standards, which are ultimately expected to improve school quality. Keywords: Assessment, Thematic Learning